A smartphone-guided secondary prevention digital health application reduces systolic blood pressure in patients with chronic coronary syndrome and insufficient blood pressure control - Philip Düsing; Stephan H. Schirmer; Sebastian Schäfer; Alexander Krogmann; Jan-Malte Sinning; Nikos Werner; Florian Bönner; Alexander Sedaghat; Cornelius Müller; Irina Eckardt; Georg Nickenig; Andreas Zietzer (Frontiers in Cardiovascular Medicine)
BackgroundChronic coronary syndrome (CCS) leads to high morbidity and mortality despite therapeutic advances in recent decades. Several modifiable risk factors, including increased blood pressure (BP), significantly contribute to cardiovascular risk in CCS. Therefore, optimal secondary prevention includes managing BP through lifestyle changes and pharmacological therapy. The CHANGE study aimed to provide evidence for optimizing secondary prevention in CCS patients using a smartphone application.MethodsThe CHANGE-Study is a prospective, randomized, controlled trial performed in 9 centers in Germany. Patients with CCS were randomly allocated to either a control or an intervention group. The intervention group received the “Vantis | KHK und Herzinfarkt” digital health application and standard care. The control group received standard care alone. From the original cohort, subgroups of patients with systolic BP ≥140 mmHg (n = 44), ≥130 mmHg (n = 89) and diastolic BP ≥90 mmHg (n = 28) were analyzed for BP reduction after 12 weeks.ResultsIn patients with systolic BP ≥140 mmHg, the intervention group showed a reduction in systolic BP by 15.5 mmHg (± 16.7 mmHg, p = 0.0001), which was greater compared to the control group (6.0 ± 13.0 mmHg, p = 0.058). This observation was consistent in patients with systolic BP ≥130 mmHg at baseline. No significant differences between both groups were observed in diastolic BP reduction in patients with diastolic BP ≥90 mmHg.ConclusionThe CHANGE study documents that a smartphone-guided digital health application positively affects systolic BP in CCS patients. This study underlines the potential of digital interventions in cardiology to improve secondary prevention.